Bruton's tyrosine kinase inhibition for the treatment of allergic disorders - Erica V. Lin; Ragha Suresh; Melanie C. Dispenza (2024)
IgE signaling through its high-affinity receptor FcεRI is central to the pathogenesis of numerous allergic disorders. Oral inhibitors of Bruton's tyrosine kinase (BTKis), which are currently FDA-approved for the treatment of B cell malignancies, broadly inhibit the FcεRI pathway in human mast cells and basophils and therefore may be effective allergen-independent therapies for a variety of allergic diseases. The application of these drugs to the allergy space was previously limited by the low kinase selectivity and subsequent toxicities of early-generation compounds. Fortunately, next-generation, highly-selective BTKis in clinical development appear to have more favorable risk-benefit profiles, and their likelihood of being FDA-approved for an allergy indication is increasing. Recent clinical trials have demonstrated the remarkable and rapid efficacy of the second-generation BTKi acalabrutinib in preventing clinical reactivity to peanut ingestion in peanut-allergic adults. Additionally, next-generation BTKis including remibrutinib effectively reduce disease activity in patients with antihistamine-refractory chronic spontaneous urticaria. Finally, several BTKis are currently under investigation in early clinical trials for atopic dermatitis and asthma. In this review, we summarize recent data supporting the use of these drugs as novel therapies in food allergy, anaphylaxis, urticaria, and other allergic disorders. We also discuss safety data derived from trials utilizing both short-term and chronic dosing of BTKis.